The Effect of “Presentation, Practice, Production’’(PPP) Method on Student Speaking Skill by Using Power Point at XI MIPA Grade - Weni Kurnia Rahmawati; Reta Prasasti; Dwi Suwita K; Abdurrahman Ahmad (Peneliti.net, 2023)
This study aims to determine the effect of the scramble learning model with the help of Power point on the students of class XI MIPA to understand the food subsection material. In addition, it also has the intention of informing students' conditions when using the Presentation, practice, production(PPP) learning model assisted by Power point learningmedia compared to Discovery learning models.This study uses a quantitative research method with a descriptive approach. So that the results obtained in the form of data that is processed in the form of a description. In addition, the data collection used is observation and interview techniques. The research population that became the object of research in this case were students of class XI MIPA 4 SMAN Pakusari, totaling 32 people.Based on the results of the research that has been carried out, positive responses were obtained from students and students who have been interviewed by researchers. Presentation, practice, production (PPP) learning models with the help of Power point here, get the results of student satisfaction in the learning obtained. From 8 informants who were randomly selected by the researchers, the results showed that the Presentation, practice,production(PPP) learning model gave them enthusiasm in learning, made it easier for students to understand the material and gave them new insights about the material being studied. With this, the Presentation,practice,production(PPP) learning model with the help of Power points has a positive influence on the students' enthusiasm for learning and makes it easier forthem to understand the material being studied.